ANALISIS KEBIJAKAN PENGEMBANGAN DAYA SAING INDUSTRI KELAPA SAWIT RIAU - Nina Nina; Suardi Tarumun; Ahmad Rifai (Indonesian Journal of Agricultural Economics, 2017)
The research aimed to analyze the competitiveness of the crude palm oil (CPO) production and formulating the improvement strategy of the International market competitiveness of the CPO in Dumai. The research was conducted in Dumai, Riau Province. The Policy Analysis Matrix (PAM) was conducted to anlyzed the competitiveness of the CPO production. The research result shows that the CPO production in Dumai was internationally competitive, it was indicated by the Domestic Ratio Cost (DRC), and it was 0.30. It has financial competitiveness also with the Private Cost Ratio of 0.12. The CPO production was gained from the combination impact of policy transfer from both tradable input and output, with the effective protection coefficient (EPC) value of 0.85. This means that government policy is not able to provide greater added value or protection by providing incentives. CPO prices do not provide real benefits to producers of CPO or palm oil farmers to produce. In addition, the profitability coefficient (PC) value was 1.07. It indicated that the financial profit was higher, it was 1.07 times higher than the social profit. Furthermore, the subsidy ratio to producers (SRP) which was the measurement from the combination of all transfer effects indicated the value of 0.05, which means divergency between the financial and social profit approximately around 5% from the gross profit. According to the PCR score which was smaller than DRC, it could be inferred that the palm oil plantation business in Dumai City is actually still in need of the government intervention to support of the International market competitiveness of the CPO.